Characterization of photosynthetic gas exchange in leaves under simulated adaxial and abaxial surfaces alternant irradiation - Zhang, Zi-Shan (Sci Rep, 2016)
Previous investigations on photosynthesis have been performed on leaves irradiated from the adaxial surface. However, leaves usually sway because of wind. This action results in the alternating exposure of both the adaxial and abaxial surfaces to bright sunlight. To simulate adaxial and abaxial surfaces alternant irradiation (ad-ab-alt irradiation), the adaxial or abaxial surface of leaves were exposed to light regimes that fluctuated between 100 and 1,000 μmol m(−2) s(−1). Compared with constant adaxial irradiation, simulated ad-ab-alt irradiation suppressed net photosynthetic rate (Pn) and transpiration (E) but not water use efficiency. These suppressions were aggravated by an increase in alternant frequency of the light intensity. When leaves were transferred from constant light to simulated ad-ab-alt irradiation, the maximum Pn and E during the high light period decreased, but the rate of photosynthetic induction during this period remained constant. The sensitivity of photosynthetic gas exchange to simulated ad-ab-alt irradiation was lower on abaxial surface than adaxial surface. Under simulated ad-ab-alt irradiation, higher Pn and E were measured on abaxial surface compared with adaxial surface. Therefore, bifacial leaves can fix more carbon than leaves with two “sun-leaf-like” surfaces under ad-ab-alt irradiation. Photosynthetic research should be conducted under dynamic conditions that better mimic nature.